Innovative approaches to address territorial multi-risk: rethinking spatial planning processes in the era of transition - Ridolfi, Vittoria; Ferraioli, Elena; Romanato, Nicola; Gerla, Federica; Magni, Filippo (Contesti. Città, territori, progetti, 2026)
In a context marked by environmental crises and interdependent vulnerabilities, this article introduces an innovative methodological approach to spatial planning based on the paradigm of multi-risk transition. The L methodology combines a vertical axis, ensuring strategic coherence across governance levels, with a horizontal axis focused on territorial multi-risk diagnosis. The article primarily explores the latter through an experimental application in the UNESCO MAB Biosphere Reserve of the Po Delta (Veneto Region). By integrating vulnerability and exposure data, the multi-risk assessment is conceived as both a cognitive and operational device to inform place-based visions and strategies. The proposed methodology serves as a transformative tool to rethink spatial planning as an adaptive governance process, capable of bridging scales, actors, and knowledge in complex territorial contexts.